2001
DOI: 10.1111/j.1936-4490.2001.tb00252.x
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Hospital Amalgamation on the Job Attitudes of Nurses

Abstract: In this longitudinal panel study we examined nurses' reactions to hospital amalgamation in both the hospitals being acquired and the acquiring hospitals. Data were collected in 1992, two years prior to the amalgamation announcement; in 1995, in the initial phase of the hospital amalgamation; and in 1997, during the amalgamation implementation. Compared with the pre‐amalgamation period, nurses in both the acquiring and the acquired hospitals reported a significant decrease in job satisfaction, organizational co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0
3

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 48 publications
0
25
0
3
Order By: Relevance
“…However the most prevalent approach to organizational commitment in the literature is one in which commitment is considered an affective or emotional attachment to the organization (Allen and Meyer 1990). Armstrong-Stassen et al (2001) found that PSS was positively related to affective commitment; therefore, the following research question was created: RQ 2: Is PSS positively related to affective commitment?…”
Section: Consequences Of Perceived Supervisory Supportmentioning
confidence: 99%
“…However the most prevalent approach to organizational commitment in the literature is one in which commitment is considered an affective or emotional attachment to the organization (Allen and Meyer 1990). Armstrong-Stassen et al (2001) found that PSS was positively related to affective commitment; therefore, the following research question was created: RQ 2: Is PSS positively related to affective commitment?…”
Section: Consequences Of Perceived Supervisory Supportmentioning
confidence: 99%
“…Em apenas 10 trabalhos (25,7%) variáveis do contexto organizacional foram efetivamente incorporadas à pesquisa. São exemplos: processo de fusão entre organizações (Armstrong-Stassen, Cameron, Mantler, & Horsburgh, 2001), processo de downsizing (Armstrong-Stassen, 2002), processo de mentoria (Donaldson, Ensher, & Grant-Vallone, 2000), movimentação na carreira (Johnston, Griffeth, Burton, & Carson, 1993). No conjunto de estudos analisados não se encontrou qualquer caso em que o contexto macrossocial fosse incorporado para ajudar a compreender a dinâmica do comprometimento organizacional.…”
Section: Dinâmica Do Comprometimentounclassified
“…No entanto, dentre os estudos, as mudanças do comprometimento tendem a estar mais relacionadas às experiências no trabalho do que a características individuais. Em alguns estudos, essas experiências são impactadas por variáveis de contexto macro como downsizing (Armstrong--Stassen, 2002), fusão (Armstrong-Stassen et al, 2001), mudanças tecnológicas (Majchrzak & Cotton, 1988), aquisição (Newman & Krzystofiak, 1993), e resultam no decréscimo do comprometimento organizacional. Os poucos dados encontrados mostram uma maior tendência ao declínio, apontando que as políticas e práticas organizacionais não estão conseguindo manter os níveis iniciais ou a predisposição dos trabalhadores em se comprometerem com as suas organizações empregadoras.…”
Section: Dinâmica Do Comprometimentounclassified
“…Armstrong-Stassen, Cameron, Mantler, Horsburgh (2001) found, in their paper examining the effects of hospital amalgamations, that trust was strongly related to job satisfaction (r=.47, p=.001) while Moss and Rowles (1997) show a difference in job satisfaction levels, depending of the characteristics of management styles. ShockleyZalabak, Ellis, Wi nog rad (2000) also looked at trust as a whole (but from a business viewpoint) and found that trust explains 60.8% of the variance in job satisfaction.…”
Section: Trust and Job Satisfactionmentioning
confidence: 99%
“…The litera ture that exists, however, does indicate that trust is an important factor in satisfac tion. Armstrong-Stassen, Cameron, Mantler, Horsburgh (2001) found in their paper, examining the effects of hospital amalgamations, that trust was strongly related to job satisfaction (r=.47, p=.001). In their paper examining burnout and nurses Laschinger, Shamian, Thomson (2001) found that while organizational trust (defined as trust that an employer will be straightforward and follow through on commitments) had relative ly low levels of direct correlation with job satisfaction, organizational trust was strongly correlated to organizational characteristics (like autonomy and decision making au thority; similar to what this study has defined as sources of job satisfaction) which were then, in turn, correlated strongly with job satisfaction.…”
mentioning
confidence: 96%